Determination of corilagin in rat plasma using a liquid chromatography–electrospray ionization tandem mass spectrometric method. (24th March 2015) - Chen, Qian Qian; Guo, Jianru; Fan, Hongyan; Wang, Caiyun; Xu, Fengguo; Zhang, Wei
ABSTRACT A sensitive and simple liquid chromatography–tandem mass spectrometric (HPLC‐MS/MS) method for the determination of corilagin in rat plasma has been developed. Samples were prepared with protein precipitation method and analyzed with a triple quadrupole tandem mass spectrometer. We employed negative electrospray ionization as the ionization source and the analytes were detected in multiple reaction monitoring mode. Separation was achieved on a C8 column eluted with mobile phase consisting of methanol–0.1% formic acid in a gradient mode at the flow rate of 0.3 mL/min. The total run time was 7.0 min.This method was proved to have good linearity in the concentration range of 2.5–1000.0 ng/mL. The lower limit of quantification of corilagin was 2.5 ng/mL. The intra‐ and inter‐day relative standard deviationa across three validation runs for four concentration levels were both <9.8%. The relative error was within ±6.0%. This assay offers advantages in terms of expediency and suitability for the analysis of corilagin in rat plasma. The practical utility of this new HPLC‐MS/MS method was confirmed in pilot plasma concentration studies in rats following oral administration. Copyright © 2015 John Wiley & Sons, Ltd.